Coronavirus Vaccine and Pregnancy: An Overview of Potential Influences and Implications for Vaccinated Women (Eurasian Medical Research Periodical, 2022)
Coronavirus disease (COVID-19) is a developing coronavirus infection (SARS-CoV-2). The majority of patients who contract COVID-19 experience mild to moderate symptoms and recover without requiring specific treatment. However, some of them will get gravely ill and require medical care. The virus can be spread from an infected person's mouth or nose by minute particles transmitted during coughing, sneezing, speaking, and breathing, or by touching a contaminated surface and then touching the eyes, nose, or mouth. Coronavirus disease 2019 (COVID-19) vaccines have begun to be distributed throughout the world, following the completion of all scientific stages of manufacture and the completion of clinical examinations of the volunteers who participated in those tests. The vaccines will be offered first to priority groups such as healthcare workers, people living in long-term care facilities, and other target groups. Several studies have proven that the various coronavirus vaccines have no adverse effect on women's fertility or capacity to conceive, and that there is no detrimental effect on pregnant women from the immunizations.